There goes the bride [large type] : an Agatha Raisin mystery - Beaton, M. C. (Beaton, M. C. Agatha Raisin mystery., 2009)
Bossy, impulsive, yet hopelessly romantic, Agatha is dreading the upcoming marriage of her ex-husband, James Lacey. Although she has set her sights on a handsome and beguiling new Frenchman, she cant quite stop obsessing about James. Her best intentions to move on with her life are put on hold when Jamess young bride is shot to death just minutes before saying I do and Agatha is named the prime suspect. Agathas sleuthing sidekick Toni stands ready to help find the real killer, but the case proves trickier than ever. Will her name be cleared, or has the outrageous Agatha finally had her last romp?